Universal screening for cardiovascular disease risk factors in adolescents to identify high-risk families: a population-based cross-sectional study. Issue 1 (December 2015) - Khoury, Michael; Manlhiot, Cedric; Gibson, Don; Chahal, Nita; Stearne, Karen; Dobbin, Stafford; McCrindle, Brian
Abstract Background Universal screening of children for dyslipidemia and other cardiovascular risk factors has been recommended. Given the clustering of cardiovascular risk factors within families, one benefit of screening adolescents may be to identify "at-risk" families in which adult members might also be at elevated risk and potentially benefit from medical evaluation. Methods Cross-sectional study of grade 9 students evaluating adiposity, lipids and blood pressure. Data collected by Heart Niagara Inc. through the Healthy Heart Schools' Program. Parents completed questionnaires, evaluating family history of dyslipidemia, hypertension, diabetes and early cardiovascular disease events in parents and siblings (first-degree relatives), and grandparents (second-degree relatives). Associations between positive risk factor findings in adolescents and presence of a positive family history were assessed in logistic regression models. Results N = 4014 adolescents ages 14–15 years were screened; 3467 (86 %) provided family medical history. Amongst adolescents, 4.7 % had dyslipidemia, 9.5 % had obesity, and 3.5 % had elevated blood pressure. Central adiposity (waist-to-height ratio ≥0.5) in the adolescent was associated with increased odds of diabetes in first- (OR:2.0 (1.6–2.6), p < 0.001) and second-degree relatives (OR:1.3 (1.1–1.6), p = 0.002). Dyslipidemia was associated with increased odds of diabetes (OR:1.6 (1.1–2.3), p < 0.001), hypertension (OR:2.2 (1.5–3.2), p < 0.001) and dyslipidemia (OR:2.2 (1.5–3.2), p < 0.001) in first degree relatives. Elevated blood pressure did not identify increased odds of a positive family history. Conclusions Presence of obesity and/or dyslipidemia in adolescents identified through a universal school-based screening program is associated with risk factor clustering within families. Universal pediatric cardiometabolic screening may be an effective entry into reverse cascade screening.